Pengaruh Struktur Aktiva, Rasio Keuangan terhadap Return on Assets pada Perusahaan Properti dan Real Estate yang Terdaftar di BEI - Restiana, Kodimah; Alie, Maria Septijantini; Yudhinanto, Yudhinanto; Nasir, M.; Oktaria, Eka Travilta (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This research aims to determine the effect of Asset Structure, Total Asset Turnover (TATO), Fixed Asset Turnover, Debt To Equity Ratio (DER), Current Ratio (CR) on Profitability Return On Assets (ROA) in Property and Real Estate companies in the Construction and Subsectors. Buildings on the Indonesian Stock Exchange for the 2016-2023. Methodology/approach: This type of research is quantitative research using the SPSS version 27 program. The analytical tool used is the classic assumption test which includes the Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Autocorrelation Test. Hypothesis testing includes Multiple Linear Regression Analysis, Determinant Coefficient Test, F Test, and T Test. Results/findings: The research results of simultaneous hypothesis testing state that Asset Structure, Total Asset Turn Over, Fixed Asset Turnover, Debt to Equity Ratio and Current Ratio have a significant effect on Return On Assets. Partial hypothesis testing states that Asset Structure, Total Asset Turn Over, Fixed Asset Turnover, and Current Ratio have a positive and significant effect on Return On Assets, while the Debt to Equity Ratio has a negative and insignificant effect on Return On Assets Conclusion: This study analyzes the impact of asset structure and financial ratios on Return on Assets in property and real estate companies listed on the IDX. The analysis results show that total assets turnover, fixed asset turnover, and debt to equity ratio have a significant effect on ROA, while the current ratio does not show a significant impact. Limitations: The use of historical data and variables is limited. The research year is only nine years with five variables Contribution: This research helps Property and Real Estate companies in the construction and building sector to see to what extent the company is able to generate profits from the assets it owns, with good marketing and management strategies.